Relationship of obesity and secondary sexual development in girls - Ida Ayu Sri Kusuma Dewi; Soetjiningsih Soetjiningsih; Yudha Patria (Paediatrica Indonesiana, 2010)
Background Obesity is a pathological condition due to consumption of excessive amount of food and is associated with early sexual maturation and irregular cycle of menstruation. Early sexual maturation is estimated from the age of menarche.Objective To determine relationship of obesity and age of secondary sexual development in girls.Methods This cross-sectional study was performed on all elementary school students in 4 sub-districts at Denpasar. Nutritional status was determined by BMI. Radiologic examination was performed to determine the bone age. Data were analyzed with appropriate statstical methods.Results Mean chronological age of breasts development for B2 and B3 stage on obese group was younger than non-obese groups (9.0 vs 9.9, P = 0.001; 9.7 vs 10.9, P = 0.006). Early menarche more frequent in obese group than non-obese groups {PR 5 (CI 95% 1.33 to 19.71)}. Mean age of children who experienced menarche on obese group was younger than non-obese group {10.9(SD 0.61) vs 11.1 (SD 0.28). Univariate analysis showed that maturation age of secondary sexual development on obese groups was differed with non-obese group {8.9 (SD 0.21) vs 9.4 (SD 0.13). Linear regression analysis showed relationship between age of breasts and pubic hair growth on both groups.Conclusions This study established that mean age of secondary sexual development was younger in obese girl than non-obese group. Bone age range on obese girls was wider than non-obese girls. [Paediatr Indones. 2010;50:49-5].